2005
DOI: 10.1162/105474605774785262
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Walking Speed in a Virtual Environment

Abstract: Studies of locomotion in virtual environments assume that correct geometric principles define the relationship between walking speed and environmental flow. However, we have observed that geometrically correct optic flow appears to be too slow during simulated locomotion on a treadmill. Experiment 1 documents the effect in a head-mounted display. Experiment 2 shows that the effect is eliminated when the gaze is directed downward or to the side, or when the walking speed is slow. Experiment 3 shows that the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
82
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(100 citation statements)
references
References 26 publications
14
82
2
Order By: Relevance
“…The scene matching task results show that subjects mostly underestimated the speed of the moving scene, regardless of mode. According to Banton et al [2005], the underestimation is due to inadequate laminar flow, which may account for some of our results. However, Durgin et al [2005a] found that these visual field speed judgments do not just depend on visual input, but also on self-motion of the subject, e.g., whether the subject was walking on a treadmill.…”
Section: Scene Speed Underestimationmentioning
confidence: 77%
“…The scene matching task results show that subjects mostly underestimated the speed of the moving scene, regardless of mode. According to Banton et al [2005], the underestimation is due to inadequate laminar flow, which may account for some of our results. However, Durgin et al [2005a] found that these visual field speed judgments do not just depend on visual input, but also on self-motion of the subject, e.g., whether the subject was walking on a treadmill.…”
Section: Scene Speed Underestimationmentioning
confidence: 77%
“…Several studies using virtual environments and Head-Mounted Displays (HMD) revealed a distance compression effect [20,23,43], partially explained by the reduced field of view and the weight and the torques exerted by the HMD on the user's head. Similarly, the perceived velocity in a VR environment differs from the real locomotion velocity [2], introducing an additional bias. Other factors, such as the image contrast [13] and the point of view [25], also influence navigation efficiency in VR.…”
Section: Perception Of Self Locomotionmentioning
confidence: 99%
“…1 Banton et al, (2005) determined that with an HMD, straight-ahead optic flow is perceived to be slower than an equivalent walking speed on the treadmill; a camera speed of 4.7 mph was used in the current experiment because it best matched a treadmill walking speed of 3 mph. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3). The VE was the same as that used in a previous treadmill study that investigated the perception of walking speed in a virtual environment (for specific details on the VE, see Banton, Stefanucci, Durgin, Fass, & Proffitt, 2005; newer hardware was used, and the golf cart was not shown). As participants walked on the treadmill, the virtual camera moved through the VE at a speed that had been determined previously to match perceived speed to the treadmill speed.…”
Section: Stimulimentioning
confidence: 99%